Comorbidities burden and previous exposure to biological agents may predict drug survival of apremilast for psoriasis in a real‐world setting. Issue 6 (13th September 2020) - Kapniari, Eirini; Dalamaga, Maria; Papadavid, Evangelia
Abstract: Apremilast is the first small molecule approved for the treatment of moderate to severe psoriasis and psoriatic arthritis in adult patients. To evaluate survival, efficacy and safety of apremilast in patients with moderate to severe psoriasis and investigate possible associations between apremilast survival and clinical parameters in a real‐world setting. In this retrospective study, a total of 71 patients who started on apremilast treatment between March 2017 and December 2019 were identified and included in the study: 40 (56.3%) males and 31 (43.7%) females, with a mean age of 55.6 ± 13.8 years and a mean Body Mass Index of 28.4 ± 6.9 kg/m 2 . At the end of the study 49.3% of patients remained on apremilast with mean treatment duration 67.2 ± 41.1 weeks (range 4‐132). Overall, mean drug survival duration was 78.51 weeks (95% CI: 65.8‐91.2 weeks). Mean drug survival was shorter when comorbidities burden was higher ( P = .012) and with previous exposure of biological agents ( P = .001). Previous exposure to biological agents (HR:3.86, 95% CI: 1.35‐11.04, P = .012) and comorbidities burden (HR: 2.27, 95% CI: 1.25‐4.12, P = .007) were independent predictors of drug discontinuation adjusting for important clinical parameters. In this real‐world setting, apremilast presented better survival rates when introduced early on the onset of moderate psoriasis, especially in biologic naïve patients with less comorbidities. More prospective and larger studies are required to determine clinical parameters affecting drug survival.